Godność człowieka i bioetyka - Wojciech Bołoz (Jesuit University Ignatianum in Krakow, 2017)
Eighteenth-century declarations of human rights referred to the Creator (the American Declaration of Independence), or the Highest Being (the French Declaration of Human Rights) as their guarantors. Progressing secularization of politics and culture made the theoreticians of human rights turn to human dignity as the value constituting the source of their being binding. Human dignity may be justified in a religious way (man has a special status, since he is created in God's own image), or in a purely rational way (the basis for a special position of man in the world is his rationality and ability to choose freely). Therefore, human dignity has become a universal value and may serve a point of reference for supporters of various world views. Special importance human dignity and his rights have nowadays in the system of international law and in bioethics. The last one protects health and life of individuals in the cases of medical interventions, especially at the beginning and at the end of human life.